2017
DOI: 10.1002/ajmg.b.32543
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D‐related genes are subjected to significant de novo mutation burdens in autism spectrum disorder

Abstract: Vitamin D deficiency is a putative environmental risk factor for autism spectrum disorder (ASD). Besides, de novo mutations (DNMs) play essential roles in ASD. However, it remains unclear whether vitamin D-related genes (VDRGs) carry a strong DNM burden. For the 943 reported VDRGs, we analyzed publicly-available DNMs from 4,327 ASD probands and 3,191 controls. We identified 126 and 44 loss-of-function or deleterious missense mutations in the probands and the controls, respectively, representing a significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 66 publications
3
22
0
Order By: Relevance
“…DNMs play essential roles in the etiology of ASD, as shown in our previous studies ( 73 75 ). We cataloged 3397 and 2285 DNMs of 2508 ASD cases and 1911 unaffected siblings, respectively, from SSC ( 79 , 80 ) (Figure 4A ).…”
Section: Results and Web Interfacesupporting
confidence: 70%
“…DNMs play essential roles in the etiology of ASD, as shown in our previous studies ( 73 75 ). We cataloged 3397 and 2285 DNMs of 2508 ASD cases and 1911 unaffected siblings, respectively, from SSC ( 79 , 80 ) (Figure 4A ).…”
Section: Results and Web Interfacesupporting
confidence: 70%
“…In addition, integrated protein-protein interaction (PPI) and co-expression networks for ASD risk genes with functional DNMs indicate that risk genes are associated with biological processes related to Wnt signaling, chromatin remodeling, transcriptional regulation, and synaptic functions [39][40][41][42][43][44] . Moreover, we previously demonstrated that DNMs and functional network analysis could provide novel insights for comparing the convergences and divergences in different ASD subcategories 45 , for investigating the genetic mechanisms of brain size-related genes 46 and vitamin-related genes 47 in ASD, and for prioritizing novel candidate genes by integrating the genetic data of different neuropsychiatric disorders 48 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the patient in the present study, there have been four cases with frameshift variants in exon 19 that have resulted in elongated amino-acid residues, two cases with PTHS (Sepp et al, 2012;Steinbusch et al, 2013), one case with autism-spectrum disorder (Li et al, 2017), and one case with abnormalities of the nervous system (Retterer et al, 2016). Patients with frameshift variants in exon 19 do not always develop typical PTHS or severe phenotypes resembling PTHS.…”
Section: The Ethics Committee Of the Institution Of Hunan Provincialmentioning
confidence: 61%